Morphometry and Organ Indices of Broilers After Supplementation of Sargassum glaucescens (J. Agardh, 1848) Ethanolic Extract - Empra, Desi Eka Putri; Hanim, Salsa Fathiyah; Bernadeth F. , Ticar; Saragih, Hendry T. S. S. G (LenteraBio : Berkala Ilmiah Biologi, 2025)
Broiler chickens are a primary protein source due to their rapid growth, which is strongly influenced by the nutrients in the feed. Sargassum glaucescens, a marine macroalgae rich in bioactive compounds, shows potential as a feed additive. This study aims to evaluate the effect of Sargassum glaucescens ethanolic extract (SGE) on broiler morphometry and organ indices. A total of 300 individual day-old broiler chicks of the Cobb 500 strain were divided into 4 treatments based on a completely randomized design, each treatment with 5 replicates consisting of 15 chickens. The treatment of SGE was given with variations of K (0% SGE/Basal Feed (BF), P1 (0.5% SGE/kg BF), P2 (1% SGE/kg BF), and P3 (2% SGE/kg BF). Parameters observed were body morphometry (beak, neck, head, back, wings, and thigh length, chest circumference, body height, and organ indices (liver, gizzard, spleen, bursa of Fabricius, intestine, and intestinal length). The results showed that SGE significantly improved morphometry and organ indices of broilers as the concentration increased. This is due to the role of flavonoids and phenolic content in increasing cell proliferation. This study concluded that the administration of SGE up to 2% was able to improve morphometry and organ indices of broilers.